Supplier Encroachment Channel Selection on an Online Retail Platform - Zongyu Mou; Kaixin Ding; Yaping Fu; Hao Sun (Systems)
Online retail platforms offer encroachment opportunities for suppliers to directly sell products to consumers on the online market. However, how to select appropriate encroachment channels poses a significant challenge for suppliers. To solve this problem, we take one supplier selling products through an indirect reselling channel on a third-party online retail platform (TORP) as the base model, and further consider that the supplier can choose TORP agency selling, the owned channel, or both to encroach onto the online market. We hereby establish game-theoretical models to analyze the optimal strategy of supplier encroachment, the TORP preference, and the equilibrium channel strategy. The findings show that the supplier is always willing to encroach onto the online market through its own channel. Additionally, when the commission rate is low, the supplier will further encroach via the TORP agency selling channel. The TORP provides the agency selling channel for the supplier only when the commission rate exceeds a certain threshold. If the channel competition is not very fierce (the competition intensity is lower than 0.852) and the commission rate is moderate, dual-channel encroachment is the equilibrium channel strategy; otherwise, supplier-owned-channel encroachment is the equilibrium strategy. We extend our main models by incorporating supplier blockchain adoption and the cost differences between both parties to enhance practical applicability.